Genocide Perspectives IV Essays on Holocaust and Genocide - Tatz, Colin (UTS ePRESS, 2012)
Genocide isn't past tense and the Nazi and Bosnian eras are not yet closed. The demonising of people as 'unworthy' and expendable is ever-present and the consequences are all too evident in the daily news. These fourteen essays by Australian scholars confront the issues: the need for a measuring scale that encompasses differences and similarities between seemingly divergent cases of the crime; the complicity of bureaucracies, the healing professions and the churches in this 'crime of crimes'; the quest for historical justice for genocide victims generally following the Nuremberg Trials; the fate of children in the Nazi and postwar eras; the 'worthiness' of Armenians, Jews and Romani people in twentieth century Europe; and the imperative to tackle early warning signs of an incipient genocide. Colin Tatz is a founding director of the Australian Institute for Holocaust and Genocide Studies, visiting fellow in Politics and International Relations at the Australian National University, and honorary visiting fellow at the Australian Institute of Aboriginal and Torres Strait Islander Studies. He teaches and publishes in comparative race politics, youth suicide, migration studies, and sports history.